Combined experimental and numerical study on the extinction limits of non-premixed H2/CH4 counterflow flames with varying oxidizer composition. (30th April 2023) - Eckart, Sven; Rong, Felix Zijie; Hasse, Christian; Krause, Hartmut; Scholtissek, Arne
Abstract: Chemical reaction mechanisms with detailed kinetics are an important topic in combustion science and an essential prerequisite for the accurate modeling of reactive flows in combustors. Besides isolating and studying individual reactions, the development of reaction mechanisms is often based on well-defined experimental observables, such as the laminar burning velocity and the ignition delay time. While many optimization targets are associated with premixed combustion, the extinction strain rate (ESR) of non-premixed flames in the counterflow configuration is another well-defined experimental observable which, however, often receives less attention. In order to reduce the scarcity of corresponding datasets for the emerging fuel hydrogen and its blends with methane, this work reports ESR measurements for H2, CH4 /H2 and CH4 counterflow diffusion flames considering a variation of the oxygen content in the oxidizer stream between 14 % and 21 %. The experimental investigation is complemented by calculations with a 1D counterflow model utilizing a temperature-control continuation method in order to determine the extinction limits numerically. The simulations are performed with six different well-established chemical reaction mechanisms. It is shown from both, experimental and numerical results, that with the substitution of CH4 by H2 the ESR increases and further, that the ESR decreases with a reduction of the oxygen content in the oxidizer stream. In addition, decreasing flame temperatures are observed at extinction as the H2 content increases. Overall, all mechanisms are able to qualitatively recover the trends found for varying H2 contents, fuel mole fraction, and oxygen content in the oxidizer. However, significant quantitative deviations are observed between the numerical results regarding the ESR values and the deviations are larger than for other important flame characteristics, such as the laminar burning velocity. The results suggest that the ESR could be a useful optimization target for further improving chemical reaction mechanisms which underlines the importance of datasets such as the one presented in this work. Highlights: Counterflow CH4, H2, and CH4 /H2 diffusion flames are investigated (exp./sim.). Variation of the oxygen content in the oxidizer stream 13.4%–21%. The qualitative trends observed in the measurements are recovered by the simulations. Significant quantitative deviations are observed between different reaction mechanisms. Extinction strain rate is a suitable optimization target for mechanism development.